Synthesis of mass exchange networks for batch processes. Part 2: Batch network design - Foo, Dominic Chwan Yee; Abdul Manan, Zainuddin; Mohd Yunus, Rosli; Abdul Aziz, Ramlan (Universiti Malaysia Sabah, 2003)
The first part of this series of papers (see (1)) presented a methodology of identifying the minimum utility targets for a mass exchange network (MEN) for a batch process. This paper describes a procedure for designing a minimum utility network. The Time-Grid Diagram (TGD) and the overall time – grid diagram (OTGD) that include the time dimension in network design have been introduced to provide a better representation of the mass exchange network for a batch process. It is desired to design a maximum mass recovery (MMR) network that will achieve the minimum utility targets set during the targeting stage of the synthesis problem [1].